2013
DOI: 10.5216/cab.v14i4.19210
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Conjuntival Em Cães Clinicamente Sadios E Cães Com Ceratoconjuntivite Seca

Abstract: Este trabalho objetivou determinar os microrganismos bacterianos no saco conjuntival de cães clinicamente normais e cães com ceratoconjuntivite seca (CCS), atendidos no Hospital de Medicina Veterinária da Universidade Federal da Bahia. Foram incluídos na pesquisa 30 animais sadios e 28 com CCS. Foi observado crescimento bacteriano em 60% das amostras oculares dos cães sadios e em 89,29% dos cães com CCS. Houve predomínio de espécies Gram positivas em ambos os grupos. Nos animais normais as bactérias mais preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
4
6
0
1
Order By: Relevance
“…This study showed similar results to those found by Oria et al (2013) to the identification of bacterial types involved in ophthalmic infections which were 64.51% of the samples identified as being Gram-positive and 35.48% Gram-negative. When compared to the identification of the bacterial genus, the present study found similar numbers to Zacarias Junior et al (2012) for Staphylococcus (66%), but higher than Oria et al (2013) with found 38%, however, similar numbers for E. coli and Enterobacter spp., 27.27% and 18.18% respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study showed similar results to those found by Oria et al (2013) to the identification of bacterial types involved in ophthalmic infections which were 64.51% of the samples identified as being Gram-positive and 35.48% Gram-negative. When compared to the identification of the bacterial genus, the present study found similar numbers to Zacarias Junior et al (2012) for Staphylococcus (66%), but higher than Oria et al (2013) with found 38%, however, similar numbers for E. coli and Enterobacter spp., 27.27% and 18.18% respectively.…”
Section: Discussionsupporting
confidence: 89%
“…When compared to the identification of the bacterial genus, the present study found similar numbers to Zacarias Junior et al (2012) for Staphylococcus (66%), but higher than Oria et al (2013) with found 38%, however, similar numbers for E. coli and Enterobacter spp., 27.27% and 18.18% respectively. As Santos et al The predominance of Gram-positive isolates is because staphylococci is part of the resident flora of the mucosa and skin, so when there is an imbalance between the agent and the host, these microorganisms can become pathogenic (Prado et al, 2005;Wang et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Similar findings were respectively reported by SANTOS et al (2009) andFOTI et al (2013) in studies with dogs and horses with healthy eyes. JOHNS et al (2011), meanwhile, reported the genus Acinetobacter as the most representative for the group of gram-negative bacteria, and did not identify Proteus mirabilis in their study.…”
Section: Resultssupporting
confidence: 80%
“…The grampositive bacteria displayed a predominance of 86.6% among the strains isolated, in accordance with findings for a series of domestic and wild animals (PRADO et al, 2005;SANTOS et al, 2009;SPINELLI et al, 2010;BONELLI et al, 2014;ORIÁ et al, 2014).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation